Yusifova, Kamala - (:unkn) unknown (My University, 2026)
Kamala Yusifova Rasim was born on August 6, 1958. She completed her secondary education at Secondary School No. 225 in Baku between 1965 and 1975. From 1975 to 1976, she worked as a draftsperson at the Tsentrosoyuzproekt Design Institute in Baku. In 1976, she enrolled in the Azerbaijan Institute of Civil Engineering, majoring in Wood Processing Technology. After graduating in 1981, she began her professional career as a design engineer in the Design Bureau of the Ministry of Wood Processing Industry. From 1983 to 1985, she worked as a part-time lecturer at the Department of Building Materials of the Azerbaijan Institute of Civil Engineering, teaching evening classes in Wood Processing Technology. In 1985, she was appointed as an Assistant Lecturer at the same department through a competitive selection process. During this period, she taught courses including Fundamentals of Artistic Design, Furniture Manufacturing Technology, Technology of Glued Wood Materials, and other related subjects. From 1995 to 2024, she served as a Senior Lecturer at the Department of Materials Science. In parallel, since 2009, she has worked part-time at the Department of Design, teaching courses such as Furniture and Interior Equipment, Technical Equipment of Interiors, Interior Typology and Classification, and other design-related subjects. In 2021, she successfully defended her doctoral dissertation entitled "The Importance of Furniture in the Design of Residential Interiors in Azerbaijan during the Twentieth Century" and was awarded the degree of Doctor of Philosophy (PhD) in Architecture in the specialty 6401.01 – Theory and History of Architecture, Restoration and Reconstruction of Architectural Monuments. In 2024, she was appointed Vice Dean for Academic Affairs of the Faculty of Design. In the same year, she was elected to the position of Associate Professor (part-time) at the Department of Environmental Design of the Faculty of Design.